Wild Montana skies [large type] - Warren, Susan May, 1966- (Warren, Susan May, 1966- Montana rescue., 2016)
"Search-and-Rescue pilot Kacey Fairing returned home to Mercy Falls, Montana, determined to put the past behind her and start a new life. But that won't be easy; her new partner is the man who broke her heart"--